MO063CHRONIC INTERSTITIAL NEPHRITIS IN AGRICULTURAL COMMUNITIES IS A TOXIN-INDUCED PROXIMAL TUBULAR NEPHROPATHY. (6th June 2020) - Vervaet, Benjamin; Nast, Cynthia; Jayasumana, Channa; Schreurs, Gerd; Roels, Frank; Herath, Chula; Kojc, Nika; Samaee, Vahid; Rodrigo, Sonali; Gowrishankar, Swarnalata; Mousson, Christiane; Dassanayake, Rajeewa; et al.
Abstract: Background and Aims: 30 years after the detection of CINAC, there is no consensus on its etiology. Heat stress/dehydration and toxic exposure are the two most likely etiologies. There are no diagnostic criteria that can directly identify CINAC patients. Method: Renal biopsies (RB) (18 Sri Lanka, 10 El Salvador, 1 India, 3 France) of patients with CINAC (CKD2-3) were examined by light (LM) and electron microscopy (EM) in comparison to RB of normal kidneys at implantation and 6 and 12 months of calcineurin inhibitor (CNI) therapy, transplant patients on CNI with indication biopsies (n=24), proteinuric nephropathies (n=15), light chain disease (n=4), cases on nephrotoxic drugs (lomustine, clomiphene, lithium, tenofovir, cisplatinum) and CKD of various causes (n=20). A rat study was conducted comparing histopathology of heat stress/dehydration with cyclosporine nephrotoxicity. Results: In addition to previously described histopathological changes, there was a unique constellation of proximal tubular cell (PTC) findings: cellular/tubular atrophy, cell fragment shedding, weak to non-proliferative capacity of the PTC and dysmorphic lysosomes increased in size and number with a light-medium electron-dense matrix containing dispersed dark electron-dense non-membrane bound "aggregates". Identical renal lesions were observed in 55-80% of renal transplant protocol biopsies taken after 6 and 12 months of calcineurin inhibitor (CNI) therapy and in indication biopsies, in implantation biopsies the prevalence was 6%. Several cases of nephrotoxic drugs (lomustine, clomiphene, lithium) and a subset of patients with light chain disease, all conditions that can be linked to CNI, presented the same lesion. Control RBs (n=66) of normal kidney, toxic nephropathies (tenofovir, cisplatinum), and overt proteinuric patients of different etiology to some extent could demonstrate the tubular cell changes observed by LM, but not or very rarely those that were observed by EM. Rats treated with cyclosporine for 4 weeks developed similar PTC lysosomal alterations, absent in a dehydration group. Conclusion: A sensitive constellation of renal PTC lesions was detected associated with CINAC and CNI nephrotoxicity in several countries, suggesting a common new paradigm where CINAC patients are experiencing a tubulotoxic mechanism similar to CNI nephrotoxicity, the latter also being known as a direct or suggested indirect effect of pesticides.